The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.bmc.2013.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Unsymmetrical 1,5-diaryl-3-oxo-1,4-pentadienyls and their evaluation as antiparasitic agents

Abstract: In this work the synthesis and antiparasitical activity of new 1,5-diaryl-3-oxo-1,4-pentadienyl derivatives are described. First, compounds 1a, 1b, 1c and 1d were prepared by acid-catalyzed aldol reaction between 2-butanone and benzaldehyde, anisaldehyde, p-N,N-dimethylaminobenzaldehyde and p-nitrobenzaldehyde. Reacting each of the methyl ketones 1a, 1b, 1c and 1d with the p-substituted benzaldehydes under basic-catalyzed aldol reaction, we further prepared compounds 2a-2p. All twenty compounds were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The compound (1 E ,4 E )-2-methyl-1,5-bis(4-nitrophenyl)penta-1,4-dien-3-one (A3K2A3) (Figure 1) is dibenzylideneacetone synthesized following the methodology described by Din et al [26]. Stock solution of the compound was prepared aseptically in DMSO and diluted in culture medium so that the DMSO concentration did not exceed 1% in the experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound (1 E ,4 E )-2-methyl-1,5-bis(4-nitrophenyl)penta-1,4-dien-3-one (A3K2A3) (Figure 1) is dibenzylideneacetone synthesized following the methodology described by Din et al [26]. Stock solution of the compound was prepared aseptically in DMSO and diluted in culture medium so that the DMSO concentration did not exceed 1% in the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, DBA potentiates TRAIL-induced apoptosis through downregulation of cell survival proteins and upregulation of death receptors via activation of reactive oxygen species (ROS) [25]. Recently, our research group reported trypanocidal activity of a DBA (1 E ,4 E )-2-methyl-1,5-bis(4-nitrophenyl)penta-1,4-dien-3-one (A3K2A3) against epimastigote and trypomastigote forms of T. cruzi [26]. …”
Section: Introductionmentioning
confidence: 99%
“…The compounds (1E,4E)-2-methyl-1-(4-nitrophenyl)-5-phenylpenta-1,4-dien-3-one (A3K2A1) and (1E,4E)-2-methyl-1,5-bis(4-nitrophenyl)penta-1,4-dien-3-one (A3K2A3) were synthesized as previously described by Ud Din et al (15). The molecular structures of the compounds are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The three forms of T. cruzi were treated with the compounds at concentrations that correspond to the IC 50 s (concentrations that inhibited 50% of the parasites) previously determined (15 MD, USA) in DMEM supplemented with 2 mM L-glutamine and 10% FBS and buffered with sodium bicarbonate in a 5% CO 2 -air mixture at 37°C (17). Trypomastigotes and amastigotes were separated by differential centrifugation at 850 ϫ g for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation